Influencia del uso de tierras diatomeas en el cultivo de arroz (Oryza sativa L.) ante el ataque de (Spodoptera frugiperda) - Botto Barros, Anllelo Xavier (2017)
VIII. SUMMARY The present research work was carried out in the Cedegé Irrigation Project, the Cedral # 2 sector, located at Km 8.0 of the Babahoyo - Montalvo road. The terrain is located at the geographical coordinates of 79 ° 32' South Latitude and 1 ° 49' West Latitude, with a height of 8 msnm, has a humid tropical climate, with an annual average temperature of 24.9 ° C, an annual average rainfall Of 1761 mm, relative humidity of 86% and 835 hours of annual average heliofania. The soil is of flat topography, clay loam texture and regular drainage. The seed material used was the SFL - 09 rice variety. The treatments consisted of several doses of the organic product plus conventional and absolute controls, such as Diatoms at doses of 1,5; 2.0 and 2.5 kg / ha, Chlorpyrifos (conventional Witness) in doses of 0.75 L / ha and an absolute Witness, without application of product. The experimental design of complete random blocks was used, with five treatments and three replicates. To determine the statistical mean between treatments, the Tukey test was used at 95% probability. For the good development of the crop, soil preparation, seeding, irrigation, weed control, fertilization, pest and disease control and harvesting were carried out. In order to estimate the effects of the treatments, the percentage of lobster incidence and severity (Spodoptera frugiperda) in rice cultivation, days at flowering, plant height, number of tillers / m2 and panicles / m2, number Grain per ear, ear length, 1000 seed weight, yield per hectare and economic analysis. From the results obtained, it was determined that the highest percentage of lobster incidence and severity (Spodoptera frugiperda) from 35 to 70 days after sowing, was reported in the absolute control; the cultivation flourished longer when Diatoms were used in doses of 2.0 kg / ha; the highest plant height was obtained with the use of Diatoms in doses of 2.5 kg / ha; the highest number of tillers / panicles / m2, grains / panicles and ear length were reached by the use of chlorophylls at doses of 0.75 L / ha as a standard control; the weight of 1000 grains was influenced by the use of Diatoms in doses of 2.5 kg / ha and the highest yield of grain and net benefit was recorded with the use of Chlorpyrifos in doses of 0.75 L / ha as conventional control with 5270.8 kg / ha and $ 749,13.